Servant leadership practices amo Servant leadership practices among secondary schools teachers of East Darfur state Eldaien loca: Servant leadership practices - Elssadig Ali Elssalih; Matebe Tafera (Universitas Islam Negeri (UIN) Sulthan Thaha Saifuddin Jambi, 2020)
The study's primary purpose was to investigate servant leadership practices among secondary schools teachers in East Darfur state Sudan. The sources of data for this research remained secondary school teachers and school principals. The primary data collection instrument was questionnaire for teachers. Besides, the sample school principals was an interview. The sample consists of 650 teachers and ten principals. Teachers were selected using simple random sampling; the school principals were selected using purposive sampling. The questionnaire was distributed to 284 teachers, and the interview was administered to 8 principals, 284 teachers, and eight principals who filled in the questionnaire and returned them. Descriptive statistics, one-sample t-test, and ANOVA test were employed in this study using SPSS to analyze the quantitative data. The qualitative data were analyzed utilizing the thematic analysis method and interview. The study's main findings indicated that there is statistical significance since it is P <0.5. There is a lower level of servant leadership practices in Eldaien secondary schools. One-Way ANOVA showed that were statistically significant differences between groups about the practices of the variables. In conclusion, the practice of servant leadership requires continuous practices to raise the level of school principals. The paper proposed research recommendations and significant suggestions. Since this study was delimited only to education in Eldaien within a single locality, in East Darfur State, the findings lack comprehensive and generalizability of the area. As a result, researchers are recommended to undertake similar research secondary schools at the national level and develop all-embracing and superior findings.